For the birds : protecting wildlife through the naturalist gaze - Cherry, Elizabeth, 1977- (Nature, society, and culture., 2019)
2020 Award for Distinguished Book from the Animals & Society Section of the American Sociological Association One in five people in the United States is a birdwatcher, yet the popular understanding of birders reduces them to comical stereotypes, obsessives who only have eyes for their favorite rare species. In real life, however, birders are paying equally close attention to the world around them, observing the devastating effects of climate change and mass extinction, while discovering small pockets of biodiversity in unexpected places. For the Birds offers readers a glimpse behind the binoculars and reveals birders to be important allies in the larger environmental conservation movement. With a wealth of data from in-depth interviews and over three years of observing birders in the field, environmental sociologist Elizabeth Cherry argues that birders learn to watch wildlife in ways that make an invaluable contribution to contemporary conservation efforts. She investigates how birders develop a "naturalist gaze" that enables them to understand the shared ecosystem that intertwines humans and wild animals, an appreciation that motivates them to participate in citizen science projects and wildlife conservation.